Characterizing the bending behavior of underground utility tunnel roofs in a fabricated composite shell system - Dong, Lei; Yao, Aijun; Zhou, Daxing; Zhang, Pengfei (Frontiers in Materials, 2023)
The traditional underground utility tunnel system is characterized by a lengthy construction period, material waste, and poor engineering quality. This study proposes the prefabricated composite shell system underground utility tunnel as a new type of prefabricated underground utility tunnel system. This system uses 20 mm thick high-performance cement-based materials as permanent templates, with steel reinforcement skeletons placed in the cavity between the two side molds, and concrete can be poured after on-site hoisting and positioning to form an integrated tunnel. This study first systematically introduces the system design method of the prefabricated composite shell system underground utility tunnel and clarifies its component and connection structures. Then, bending tests are conducted on the composite shell tunnel top plate specimens, and a cast-in-place top plate specimen is selected as a control group. A suitable bearing capacity calculation formula for composite shell top plates is derived and proposed based on test phenomena and results analysis. The results showed that the prefabricated outer template and internal cast-in-place concrete of the composite shell top plate specimen have good collaborative performance. Its bearing capacity, stiffness, and failure phenomena are consistent with those of cast-in-place components, as are its mechanical properties. In addition, the proposed bearing capacity calculation formula for a composite shell top plates is highly accurate and can guide the design of such components.